Pengecekan Tekanan Darah dan Kolesterol pada Masyarakat RT 01/ RW 09 Kelurahan Porisgaga, Kota Tangerang, Banten, Indonesia: Pengecekan Tekanan Darah dan Kolesterol pada Masyarakat RT 01/ RW 09 Kelurahan Porisgaga, Kota Tangerang, Banten, Indonesia - Anggraeni, Indri Putri; Wijoyo, Eriyono Budi; Winahyu, Karina Megasari (Ruang Ide Publisher, 2025)
The incidence of non-communicable diseases in Indonesian society, especially in big cities like Tangerang, is still relatively high. Non-communicable diseases such as hypertension and cholesterol, especially in adults over 18 years old, are high. Community service will be conducted in Tangerang City, especially in Porisgaga Village, where hypertension and cholesterol occur. Hypertension and cholesterol problems can be identified by first conducting an examination. Examination by health workers is one of the parameters to determine the normal limits of the disease. Cholesterol is often considered harmful because of its association with cardiovascular disease, even though it has a vital role in various biological functions. Therefore, an initial examination is needed to determine the disease suffered. This activity was carried out on 17 people by examining blood pressure and cholesterol. This community service found that 52.9% of people had high hypertension, and 23.5% had high cholesterol. There needs to be an effort to educate people and change their lifestyles to prevent more serious diseases in the future.